Management, Exploitation and Contract Labor of the Pine Merkusi Forest in Tanah Gayo during the Dutch Colonial Period - Iswanto, Sufandi; Nurasiah, Nurasiah; Kusnafizal, Teuku; Haikal, Muhammad; Zulfan, Zulfan; Azis, Abdul; Ramazan, Ramazan (Forest and Society, 2022)
This article examined the history of the merkus pine forest in the Dutch colonial era in Tanah Gayo, Aceh Province, Indonesia. The researcher focused on finding facts about (1) forest management and exploitation; and (2) the life of the contract labor. In this study, we employed the historical method using primary sources, which consisted of documents or archives, reports, pictures, and records of the Dutch people’s journey to Tanah Gayo. In addition, the secondary sources were books, newspapers, thesis, and relevant articles. The author found three very basic problems. First, before the arrival of the Dutch colonials, most of the merkus pine forest was part of ulayat lands and customary forests. The forest itself was regulated by custom and maight not be owned by individuals. In addition, the community was traditionally given the right to use the resources in the forest. During the Dutch colonial period, the forest management system adopted many systems and rules from Java, but these rules were interpreted by the Dutch according to the purpose of exploitation so that it seemed unclear. Second, the contract labor were Javanese, but these workers were actually part of human exploitation.